Organic solid-state lithium secondary battery

By using specific positive electrode materials and TPFPB-improved organic solid electrolytes in organic solid lithium secondary batteries, a stable interface is formed, and the problem of instability of organic solid electrolytes at high voltages is solved, and a lithium battery with high energy density and safety is achieved, suitable for lithium metal and lithium ion batteries.

CN119786710APending Publication Date: 2025-04-08SHANGHAI INSTITUTE OF APPLIED PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411717351.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing organic solid electrolytes are unstable at high voltages, are easy to oxidize and decompose, and have poor compatibility with high voltage positive electrode materials, which limits the energy density of lithium batteries.

Method used

Using organic solid lithium secondary batteries, a ternary positive electrode material with a LiCoO2 or Ni content greater than 60%. The negative electrode material is lithium metal, Si negative electrode, etc. Combined with PDADMATFSI/LiTFSI/PI+TPFPB organic solid electrolyte, a stable positive electrode solid electrolyte interface is formed during the charging process through TPFPB additives, which inhibits oxidation and decomposition, and forms a stable interface on the negative electrode to improve compatibility.

Benefits of technology

It realizes the high energy density and safety of lithium batteries at high voltages. The charging voltage can reach 4.6V vs. Li/Li+, and the energy density exceeds 500Wh/kg. It has high safety and low cost. It is suitable for lithium metal batteries and lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786710A_ABST
    Figure CN119786710A_ABST
Patent Text Reader

Abstract

The invention relates to an organic solid-state lithium secondary battery which comprises a positive electrode, a negative electrode and organic solid electrolyte, the positive electrode material is LiCoO2 or ternary positive electrode material lithium with the Ni content larger than 60%, the negative electrode material is a lithium metal negative electrode, a Si negative electrode, a graphite negative electrode or a lithium titanate negative electrode, and the organic solid electrolyte is PDADMATFSI and LiTFSI which are added with TPFPB and loaded on PI. According to the organic solid-state lithium secondary battery, the organic solid-state electrolyte material is matched with the positive electrode material and the negative electrode material to obtain the organic solid-state lithium secondary battery, and the organic solid-state lithium secondary battery has high working voltage, high energy density and high safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid-state lithium battery, and more particularly to an organic solid-state lithium secondary battery. Background Art

[0002] Renewable energy replacing traditional fossil energy is crucial to achieving the goal of "dual carbon". The efficient use of clean energy such as wind energy and solar energy is inseparable from the development and application of large-scale energy storage systems. Among many energy storage systems, electrochemical energy storage systems are expected to be applied to large-scale energy storage due to their advantages such as high volume and mass energy density and flexible installation. In addition, lithium-ion batteries have been widely used in portable electronic devices, electric vehicles and large-scale energy storage due to their excellent electrochemical properties. Most of the widely used lithium-ion batteries currently use liquid electrolytes. The organic solvents in the liquid electrolyte are flammable, which brings certain safety risks to the battery. In addition, most organic solvents have side reactions with lithium metal, and lithium metal cannot be used as the negative electrode, which limits the energy density of lithium batteries. The solid-state battery constructed by replacing the traditional liquid electrolyte with a solid electrolyte has the advantages of being non-flammable, high temperature resistant, non-corrosive, non-volatile and having good compatibility with lithium metal, and is considered to be one of the important development directions of lithium secondary batteries. Solid-state batteries have high advantages in safety and energy density, which will subvert the existing lithium battery technology dominated by liquid electrolytes and are expected to become the next generation of high-performance batteries. By developing new key solid electrolyte materials, we can build solid-state batteries with excellent performance and subvert existing lithium battery technology.

[0003] As one of the core materials of solid-state batteries, solid electrolyte plays a decisive role in the performance of solid-state batteries. Therefore, the development of solid electrolyte materials with excellent performance is of great significance to improving the performance of solid-state batteries. The current main solid electrolytes include inorganic ceramic compounds, sulfides, halides, organic polymer compounds, etc., but solid-state batteries built based on these material systems still face many problems and challenges, and their performance needs to be further improved. Among them, organic solid electrolytes have the advantages of relatively high ionic conductivity, low interfacial impedance, easy preparation, and low cost, showing great application prospects. However, most polymer solid electrolytes are unstable under high voltage and are easily oxidized and decomposed, which makes this type of solid electrolyte poorly compatible with high-voltage positive electrode materials (high-voltage LiCoO2, high Ni ternary (Ni content greater than 60%), spinel nickel manganese oxide), which seriously limits the energy density of lithium batteries. The previous solution was to use positive electrode materials with relatively low working voltages, such as LiFePO4, sulfur (S); or to match high-voltage LiCoO2, high Ni ternary (Ni content greater than 60%), but the charging cut-off voltage is generally less than 4.2V vs. Li / Li + , which severely limits the energy density of the battery. Summary of the invention

[0004] In order to solve the problems in the prior art such as the narrow voltage window of the existing organic solid electrolyte, which limits the energy density of the solid-state lithium secondary battery, the present invention provides an organic solid-state lithium secondary battery.

[0005] According to the organic solid-state lithium secondary battery of the present invention, it includes a positive electrode, a negative electrode and an organic solid electrolyte, wherein the positive electrode material is LiCoO2 or a ternary positive electrode material lithium with a Ni content greater than 60%, the negative electrode material is a lithium metal negative electrode, a Si negative electrode, a graphite negative electrode or a lithium titanate negative electrode, and the organic solid electrolyte is PDADMATFSI and LiTFSI loaded on PI with TPFPB added.

[0006] In a preferred embodiment, the positive electrode material is LiNi x Co y Mn z O2, x is greater than 60%, x+y+z=1.

[0007] In a preferred embodiment, the positive electrode material is LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0008] In a preferred embodiment, the negative electrode material is Li-C, Li-Zn, Li-Al, Li-Cu, Li-Ag, Si / C or SiO x negative electrode.

[0009] In a preferred embodiment, the organic solid-state lithium secondary battery is a lithium metal battery or a lithium ion battery.

[0010] In a preferred embodiment, the operating voltage of the lithium metal battery is 2.7-4.6V, and the operating voltage of the lithium ion battery is 2.7-4.4V.

[0011] According to the organic solid-state lithium secondary battery of the present invention, an organic solid-state electrolyte material PDADMATFSI / LiTFSI / PI+TPFPB is used, wherein the introduction of the TPFPB additive can form a stable positive electrode solid electrolyte interface (CEI) during the charging process, effectively protect the positive electrode material, and inhibit the oxidative decomposition of the organic solid electrolyte material. The organic solid-state lithium secondary battery obtained by combining the positive and negative electrode materials has a high operating voltage, a high energy density and a high safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 is Li||PDADMATFSI / LiTFSI / PI+TPFPB||LiNi according to Example 1 of the present invention 0.8 Co 0.1 Mn0.1 Schematic diagram of the structure of O2 solid-state lithium metal battery.

[0013] Figure 2 is Si||PDADMATFSI / LiTFSI / PI+TPFPB||LiNi according to Example 2 of the present invention 0.8 Co 0.1 Mn 0.1 Schematic diagram of the structure of O2 solid-state lithium-ion battery.

[0014] Figure 3 It is a schematic structural diagram of the Li||PDADMATFSI / LiTFSI / PI+TPFPB||LiCoO2 solid-state lithium metal battery according to Example 3 of the present invention.

[0015] Figure 4 It is a schematic structural diagram of the Si||PDADMATFSI / LiTFSI / PI+TPFPB||LiCoO2 solid-state lithium-ion battery according to Example 4 of the present invention. DETAILED DESCRIPTION

[0016] The following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings.

[0017] The invention provides an organic solid-state lithium secondary battery, which comprises a positive electrode, a negative electrode and an organic solid electrolyte.

[0018] The positive electrode material is LiCoO2 or a ternary positive electrode material lithium with a Ni content greater than 60%. In a preferred embodiment, the ternary positive electrode material is a nickel cobalt manganese oxide positive electrode. In a preferred embodiment, the nickel cobalt manganese oxide positive electrode is LiNi x Co y Mn z O2 positive electrode material, x is greater than 60%, x+y+z=1, such as LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0019] The negative electrode material is a lithium metal negative electrode, a Si negative electrode, a graphite negative electrode or a lithium titanate negative electrode. In a preferred embodiment, the lithium metal negative electrode is pure lithium metal or a lithium metal composite material, such as Li-C (carbon), Li-Zn, Li-Al, Li-Cu, Li-Ag, etc. In a preferred embodiment, the Si negative electrode is a single silicon negative electrode, a Si / C negative electrode, a SiO x Negative pole, etc.

[0020] The organic solid electrolyte is PDADMATFSI / LiTFSI / PI+TPFPB, which is composed of polydimethyldiallyl ammonium bis(trifluoromethylsulfonyl)imide (PDADMATFSI), bis(trifluoromethanesulfonyl)imide lithium (LiTFSI) (mass ratio 1:1), and 3% tris(pentafluorophenyl) borane (TPFPB) added, which is loaded on a polyimide (PI) film. + With TFSI from PDADMATFSI and LiTFSI - There is a co-coordination relationship (i.e. PDADMA - +TFSI - +Li + Co-coordination), adding anion receptor TPFPB to bind TFSI - Anions promote the migration of lithium ions. At the same time, TPFPB can decompose at high voltage to produce a positive electrode solid electrolyte interface (CEI) and a negative electrode solid electrolyte interface (SEI). It has good compatibility (electrochemical stability) with positive and negative electrode materials, and the charging cut-off voltage can reach 4.6V vs.Li / Li + Different from the traditional PEO-based organic solid electrolyte, the oxidation voltage is less than 4.0V vs.Li / Li + , the positive electrode material can generally only choose LiFePO4 or sulfur (S) positive electrode, or low-voltage LiCoO2, etc. In particular, the PDADMATFSI / LiTFSI / PI+TPFPB organic solid electrolyte material is oxidatively decomposed under high voltage, and the electrochemical in-situ CEI protective layer is loaded on the electrode surface, stabilizing the interface and increasing the charging voltage of the solid-state battery. In addition, the additive TPFPB is a very good flame retardant material, which greatly improves the safety of the battery system. Moreover, the PI substrate has high temperature resistance, and compared with PEO-based solid electrolyte materials, the high temperature resistance and safety are greatly improved.

[0021] Lithium secondary batteries include lithium metal batteries and lithium ion batteries. The difference lies in the negative electrode. Lithium metal batteries use lithium metal as the negative electrode material, while lithium ion batteries use graphite, Si, Si / C, etc. as the negative electrode material. The output voltage of the organic solid-state lithium metal battery known in the prior art is less than 4.3V, and the corresponding energy density is less than 500Wh / kg. The output voltage of the organic solid-state lithium metal battery according to the present invention is greater than 4.6V, and the energy density is greater than 500Wh / kg. The output voltage of the organic solid-state lithium ion battery known in the prior art is less than 4.1V, and the corresponding energy density is less than 400Wh / kg. The output voltage of the organic solid-state lithium ion battery according to the present invention is greater than 4.4V, and the energy density is greater than 400Wh / kg. In addition, the lithium secondary battery has a simple preparation process, low cost, good wide temperature performance and excellent safety.

[0022] Example 1

[0023] positive electrode

[0024] LiNi 0.8 Co 0.1 Mn 0.1 O2 is the positive electrode material, the conductive agent Super P, and the binder PVDF are mixed in a mass ratio of 90:5:5 to prepare a slurry, which is then coated on the Al current collector. The positive electrode is obtained after drying, rolling, cutting, and weighing.

[0025] Synthesis of PDADMATFSI via ion exchange method

[0026] 20g 20wt.% polydimethyldiallyl ammonium chloride (PDADMACl) aqueous solution was mixed with 100mL deionized water for dilution, and the resulting solution was recorded as solution A. 8.52g LiTFSI was weighed and dissolved in 20mL deionized water, and the resulting solution was recorded as solution B. Under stirring, solution B was dripped dropwise into solution A, and a white precipitate was immediately produced. The resulting mixed system was recorded as C. After 2 hours of stirring reaction, C was filtered, the resulting precipitate was collected, and deionized water was then added to the precipitate, washed by stirring, and the washing time was not less than 0.5 hours, and then filtered again. According to the above-mentioned washing method, the precipitate was washed more than five times and detected with a silver nitrate solution until no precipitation was detected in the washing solution. The washed product was placed in a 90°C blast oven and dried for 2 hours, and then the product was transferred to a vacuum drying oven at 105°C and continued to dry for 24 hours to further remove residual moisture. After drying, the product was taken out and ground into powder. Finally, the powder sample was placed in a vacuum drying oven and vacuum dried at 105°C for 24 hours to ensure that the product was completely dried. The final product was a pure white powder.

[0027] Preparation of electrolyte membrane by solution casting method

[0028] 100 mg of tri(pentafluorophenyl)borane (TPFPB) was added to 10 mL of DMF, and after stirring and dissolving, a TPFPB solution with a concentration of 10 mg / mL was obtained. In a glove box, 0.3 g of PDADMATFSI was first dissolved in 900 μL of 10 mg / mL TPFPB solution, and then 300 μL of DMF was added. After stirring for 0.5 hours, 0.3 g of LiTFSI was added, and stirring was continued for 12 hours to obtain a transparent slurry with a certain viscosity. The polyimide film (PI film) was fixed on a polytetrafluoroethylene plate, and the slurry obtained above was scraped on the PI film with a scraping thickness of 200 μm, and then placed in a vacuum oven at 60°C and dried under vacuum conditions for 24 hours to obtain an electrolyte membrane, which was dried and cut for use. It should be understood that by accurately controlling the amount of 10 mg / mL TPFPB solution added, electrolyte membranes with different TPFPB doping amounts can be prepared.

[0029] Assembly

[0030] Lithium metal as negative electrode material, PDADMATFSI / LiTFSI / PI+TPFPB solid electrolyte, LiNi 0.8 Co 0.1 Mn 0.1 O2 is used as the positive electrode material to assemble solid-state lithium metal batteries, such as Figure 1 shown.

[0031] The assembled solid-state lithium metal battery was subjected to constant current charge and discharge test on an electrochemical measuring instrument. The constructed battery can be charged and discharged in cycles at 2.7-4.6V. It exhibits a reversible capacity of 225mAh / g (C / 10) and an energy density of 512Wh / kg, as shown in Table 1 below, and exhibits a reversible capacity of 160mAh / g under 2C conditions. It should be understood that the fully charged state is defined as 100% SOC, the powerless state is defined as 0% SCO, and 2C refers to the time taken from 0-100% SOC and 100%-0% state, respectively, for 30mins.

[0032] Example 2

[0033] LiNi 0.8 Co 0.1 Mn 0.1O2 is used as the positive electrode material, the conductive agent Super P, and the binder PVDF are mixed in a mass ratio of 90:5:5 to prepare a slurry, which is then coated on the Al current collector. After drying, rolling, cutting, and weighing, the positive electrode is obtained. PDADMATFSI is synthesized by ion exchange. Then in the glove box, 0.3g PDADMATFSI is dissolved in 900μL of a pre-prepared 10mg / mL TPFPB solution, and then 300μL DMF is added. After stirring for 0.5 hours, 0.3g LiTFSI is added and stirring is continued for 12 hours to obtain a transparent slurry with a certain viscosity. The polyimide film (PI film) is fixed on a polytetrafluoroethylene plate, and the above-obtained slurry is scraped on the PI film with a scraping thickness of 200μm, and then placed in a vacuum oven at 60°C and dried under vacuum conditions for 24 hours to obtain an electrolyte membrane. After drying and cutting, it is ready for use. Using high-capacity Si as the negative electrode material, PDADMATFSI / LiTFSI / PI+TPFPB solid electrolyte, LiNi 0.8 Co 0.1 Mn 0.1 O2 is used as the positive electrode material to assemble solid-state lithium-ion batteries, such as Figure 2 The constructed lithium-ion battery exhibits a reversible capacity of 195 mAh / g (C / 10) and an energy density of more than 421 Wh / kg in a charge-discharge cycle at 2.7-4.4 V, as shown in Table 1 below.

[0034] Example 3

[0035] LiCoO2 was used as the positive electrode material, the conductive agent Super P, and the binder PVDF were mixed in a mass ratio of 90:5:5 to prepare a slurry, which was then coated on the Al current collector. After drying, rolling, cutting, and weighing, the positive electrode was obtained. The synthesis of PDADMATFSI was carried out by ion exchange. Then in the glove box, 0.3g PDADMATFSI was dissolved in 900μL of a pre-prepared 10mg / mL TPFPB solution, and then 300μL DMF was added. After stirring for 0.5 hours, 0.3g LiTFSI was added and continued to stir for 12 hours to obtain a transparent slurry with a certain viscosity. The polyimide film (PI film) was fixed on a polytetrafluoroethylene plate, and the slurry obtained above was scraped on the PI film with a scraping thickness of 200μm, and then placed in a vacuum oven at 60℃ and dried under vacuum conditions for 24 hours to obtain an electrolyte membrane. After drying and cutting, it was set aside. Solid-state lithium metal batteries were assembled using lithium metal as the negative electrode material, PDADMATFSI / LiTFSI / PI+TPFPB solid electrolyte, and LiCoO2 as the positive electrode material. Figure 3The constructed battery can be charged and discharged in cycles at 2.7-4.6 V. It exhibits a reversible capacity of 210 mAh / g (C / 10) and an energy density of 505 Wh / kg, as shown in Table 1 below.

[0036] Example 4

[0037] LiCoO2 was used as the positive electrode material, the conductive agent Super P, and the binder PVDF were mixed in a mass ratio of 90:5:5 to prepare a slurry, which was then coated on the Al current collector. After drying, rolling, cutting, and weighing, the positive electrode was obtained. The synthesis of PDADMATFSI was carried out by ion exchange. Then in the glove box, 0.3g PDADMATFSI was dissolved in 900μL of a pre-prepared 10mg / mL TPFPB solution, and then 300μL DMF was added. After stirring for 0.5 hours, 0.3g LiTFSI was added and continued to stir for 12 hours to obtain a transparent slurry with a certain viscosity. The polyimide film (PI film) was fixed on a polytetrafluoroethylene plate, and the slurry obtained above was scraped on the PI film with a scraping thickness of 200μm, and then placed in a vacuum oven at 60℃ and dried under vacuum conditions for 24 hours to obtain an electrolyte membrane. After drying and cutting, it was set aside. Solid-state lithium-ion batteries were assembled using high-capacity Si as the negative electrode material, PDADMATFSI / LiTFSI / PI+TPFPB solid electrolyte, and LiCoO2 as the positive electrode material. Figure 4 The solid-state lithium-ion battery constructed exhibits a reversible capacity of 194 mAh / g (C / 10) and an energy density of 450 Wh / kg in a charge-discharge cycle at 2.7-4.4 V, as shown in Table 1 below.

[0038] Table 1 Comparison of electrochemical performance of all-solid-state lithium secondary batteries using different positive electrode materials, negative electrode materials, and solid electrolytes

[0039]

[0040] The organic solid-state lithium secondary battery according to the present invention adopts a high-voltage positive electrode material, a high-capacity negative electrode material and a PDADMATFSI / LiTFSI / PI+TPFPB organic solid electrolyte. In the electrochemical process, the TPFPB organic matter is oxidized and decomposed to form a stable CEI interface on the surface of the positive electrode material. The organic solid-state lithium secondary battery thus obtained exhibits high voltage stability, high output voltage (operating voltage up to 4.6V) and high energy density (energy density higher than 400Wh / kg), and exhibits excellent electrochemical performance. At the same time, the electrolyte is a solid electrolyte, which has the advantages of high temperature resistance and non-flammability compared with liquid electrolytes, and exhibits high safety characteristics. The preparation process is simple, and low interface impedance can be ensured without any interface modification steps. It has the advantages of high safety, low cost, easy industrialization, etc., and has broad application prospects.

[0041] The above is only a preferred embodiment of the present invention, and is not intended to limit the scope of the present invention. The above embodiment of the present invention can also be modified in various ways. That is, all simple, equivalent changes and modifications made according to the claims and the description of the present invention fall within the scope of protection of the claims of the present invention. The contents not described in detail in the present invention are all conventional technical contents.

Claims

1. An organic solid-state lithium secondary battery, characterized in that: The organic solid-state lithium secondary battery includes a positive electrode, a negative electrode and an organic solid electrolyte, wherein the positive electrode material is LiCoO2 or a ternary positive electrode material lithium with a Ni content greater than 60%, the negative electrode material is a lithium metal negative electrode, a Si negative electrode, a graphite negative electrode or a lithium titanate negative electrode, and the organic solid electrolyte is PDADMATFSI and LiTFSI loaded on PI with TPFPB added.

2. The organic solid-state lithium secondary battery according to claim 1, characterized in that: The positive electrode material is LiNi x Co y Mn z O2, x is greater than 60%, x+y+z=1.

3. The organic solid-state lithium secondary battery according to claim 2, characterized in that: The positive electrode material is LiNi 0.8 Co 0.1 Mn 0.1 O2.

4. The organic solid-state lithium secondary battery according to claim 1, characterized in that: The negative electrode material is Li-C, Li-Zn, Li-Al, Li-Cu, Li-Ag, Si / C or SiO x negative electrode.

5. The organic solid-state lithium secondary battery according to claim 1, characterized in that: Organic solid-state lithium secondary batteries are lithium metal batteries or lithium ion batteries.

6. The organic solid-state lithium secondary battery according to claim 5, characterized in that: The operating voltage of lithium metal batteries is 2.7-4.6V, and the operating voltage of lithium ion batteries is 2.7-4.4V.